Substrate‐dependent enhancement of the durability of EPD graphene coating as a macroscale solid lubricant. (22nd May 2022) - Chen, Sulin; Hong, Hong; Shen, Bin
Abstract : Graphene has exhibited outstanding properties of reducing friction and wear when it is utilized as a novel solid lubricant, while its durability, especially at the macroscale, remains a challenge for robust industrial applications. In this study, we demonstrate a remarkable substrate‐dependent enhancement of the durability and load capacity of graphene film prepared with electrophoretic deposition method. The tribological performance of graphene films on four typical engineering material surfaces was examined. Graphene films exhibit highly consistent coefficients of friction ranging from 0.1 to 0.16, decreasing by 76%–87% compared with that obtained for the bare substrates (0.60–0.83). As for durability, graphene films on the stainless steel and titanium alloy substrates show largely enhanced lifetime compared with that on the silicon or cemented carbide substrates. The graphene film on titanium allay can sustain up to 260, 000 cycles, 10–20 times longer than that on brittle substrates. Such a remarkably enhanced durability should be attributed to the relatively higher ductility of the substrates and its high adhesion with graphene, which is beneficial for forming a dense layer of graphene‐containing tribo‐film within the sliding interface. The results of this study may provide a useful guideline for utilizing graphene films as solid lubricants in engineering fields.